Y-chromosome DNA haplotypes in human samples from Bahia, Brazil - Santos, M. V. (2003)
Background: The Y-chromosome polymorphisms have a great value to population genetic studies and evolutionary aspects since these markers show high levels of heterogeneity within and between populations, permitting the geographical distribution and ancestry of patrilineages to be evaluated. They complement the autosomal STRs and mtDNA matrilineage information. Y-linked STRs remain stable in given paternal lineages over many generations so they are useful for identification in forensic cases, namely in criminal stain with male/female contributions. Methods: In this study, we report Y-chromosome haplotypes in a population sample with 68 unrelated males blood donors from Bahia state (Northeastern Brazil). The Y-STRs (DYS19, DYS389 I/II, DYS390 and DYS393) were determined after PCR pentaplexing with an automatic ABI sequencer. Results: In the Bahia population, we observed 47 different Y-chromosome haplotypes, of which 37 Y-haplotypes were unique. Only two Y-types were present in more than two persons. The most significant values of gene diversity were found in the markers DYS390, DYS389 II and DYS19 in decreasing order. The haplotype diversity value of the population studied was of 96.62. Conclusion: Comparing this Brazilian population with other Brazilian, Portuguese and African populations, we observed that the Bahia population has a similar haplotype diversity value to other Brazilian and Portuguese populations.